Multisymptom Illness in Gulf War Veterans: A Systematic Review and Meta-Analysis. Issue 7 (July 2016) - Gwini, Stella M.; Forbes, Andrew B.; Sim, Malcolm R.; Kelsall, Helen L.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: The aim of this study was to conduct a systematic review and meta-analysis of multisymptom illness (MSI) in 1990 to 1991 Gulf/Afghanistan/Iraq War veterans. Methods: Electronic databases were searched from January 1990, June 2014 for studies on MSI prevalence in Gulf/Afghanistan/Iraq War veterans, based on the Centers for Disease Control and Prevention MSI case definition, and which included a military comparison group. Results: Seven studies were identified among US, UK, and Australian Gulf War veterans; no studies were identified in Afghanistan/Iraq War veterans. MSI prevalence in Gulf War veterans and comparison groups ranged from 26 to 65% and from 12 to 37%, respectively. More recent studies were larger, with improved designs. The pooled odds ratio comparing Gulf War veterans to other military groups was 2.74 (95% confidence interval 2.15 to 3.51). Conclusion: The systematic review showed that MSI was most prevalent in Gulf War veterans, emphasizing the health burden of MSI in this veteran population.